المدخل في الاختبار اللغوي - Dian Ekawati (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2017)
The approach is one of the components of learning. It is a strarting point of point of view of the teacher in the teacing-learning process.It refers to the nation about the occurence of a process of a general nature. The learning approach, broadly, is devided into two categories, namely teacher-centered and student-centered approach. A teacher, in teacher-centered approach, plays a role as an expert and center of learning that promotes his good experience in order to inspire and simulate the students.While, in the student-centered appoach, a role of teacher is just as a motivator and facilitator of leearning that encourages the students to be actively involved in teacheng-learning process. Some following approaches can be applied in the language learning and evaluation, that is: traditional approach, discrete approach, integrative approach, pragmatic and communicative approach.